Grammatical Competence within L2 Communication: Language Production, Monitor Hypothesis, and Focus on Forms Instruction - Moh. Rofid Fikroni (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Bearing in mind that the learners’ speaking skill had become the main goal in learning language, grammatical competence is believed to have a big role within foreign language learners’ language production, especially in spoken form. Moreover, the learners’ grammatical competence is also closely related to the Monitor Hypothesis proposed by Krashen (1982) in which it says that the acquired system will function as monitor or editor to the language production. The students’ monitor performance will vary based on how they make use of their acquired system. They may use it optimally (monitor optimal user), overly (monitor over-user), or they may not use it at all (monitor under-user). Therefore, learners’ grammatical competence has its own role, which is very crucial, within learners’ language production, which is not only to produce the language, but also to monitor the language production itself. Because of this reason, focus on form instruction will give a great impact for students’ grammatical competence within their communicative competence. This paper aims to present ideas about the how crucial the role grammatical competence within learners’ L2 communication.